LOCAL WISDOM IN MA’BALENDO’S TRADITIONAL ARTS AT THE HARVEST FESTIVAL IN BELOPA, LUWU REGENCY - Syamzan Syukur; Wahyuddin Gudang; Rahmat Rahmat (Balai Penelitian dan Pengembangan Agama Makassar, 2022)
AbstractThis research discussed in this paper the elements of local wisdom in the traditional art of Ma’balendo during the harvest party in Belopa, Luwu Regency. The goal of this research is to reveal the importance of local wisdom in the Ma’balendo traditional art form.The findings of this study can be used to manage life, build and organize the Luwu community's culture and civilization. Furthermore, this research can be used as a reference for future research studying Luwu's culture and development.This research is field research intended to gather and analyze the data qualitatively. It addressed the issues using historical, anthropological, and hermeneutic approaches. The data were collected through observation, in-depth interviews, and documentation. Meanwhile, the data processing and analysis technics used data reduction, presentation, and drawing conclusions or verification.The results of this research indicate that the traditional art of Ma’balendo, as the original ancestral heritage of the Luwu people, is an art performance with farming activities as its theme. The art contains many peculiarities and uniqueness, even the art is full of local wisdom, among others; 1) spiritual dimension, 2) social and community dimension, 3) educational and moral dimension, 4) gender relation dimension in people's lives, and 5) art or entertainment dimension.This research differs from the earlier research, yet the findings will fill in the gaps and contribute to the content of the prior studies. Additionally, the findings of this study can be used as a reference for future research.